High-adhesive and conductive AMPSs-TA-Fe hydrogels via E-beam-assisted rapid one-pot synthesis for strain sensor - Eunhye Kim; Heewoong Park; Ngo Thi Hang; Daewoo Kim; Seunghan Shin; Kiok Kwon (Polymer Testing)
The development of high-performance hydrogels with high ionic conductivity, mechanical stability, and exceptional skin adhesion, even under wet conditions, is crucial for advancements in wearable electronics. With abundant hydroxyl groups, tannic acid (TA) is renowned for its adhesion to skin in moist environments, facilitated by coordination bonds with metal ions such as Fe3+. However, TA's radical scavenging effect complicates polymerization by UV or thermal curing, leading prior studies to adopt time-intensive, costly approaches, such as post-polymerization soaking or pre-formed polymers. Here, we used E-beam irradiation for rapid, one-pot in situ polymerization from a precursor solution of 2-Acrylamido-2-methylpropanesulfonic acid sodium salt (AMPSs), TA, and Fe ions, incorporating all components in a single step. We report the successful synthesis of a multifunctional hydrogel with exceptional skin adhesion, high ionic conductivity, strong mechanical strength, excellent recovery, and self-healing properties, all achieved through a simple one-pot electron beam curing method in just 13.89 s. This remarkable curing time contrasts with the lengthy durations (1–8 h) of conventional TA-incorporating methods, eliminating the need for heat or UV initiators. The resulting P(AMPSs-TA-Fe) hydrogel exhibited high skin adhesion (154.53 N/m) due to TA-Fe coordination and excellent ionic conductivity (2.71 S/m) from AMPSs, Fe3+ ions, and TA's ion-bridging effect. The reversible TA-Fe bonding also imparted strong fatigue resistance (1.32 kJ/m3 at 200 % strain) and self-healing, enabling conductivity recovery within 2.4 s after damage. Overall, the P(AMPSs-TA-Fe) hydrogel shows great promise for flexible sensors, combining robust mechanical performance, excellent skin adhesion, high ionic conductivity, and rapid self-healing.